The Influence of Financial Literacy, Family Economic Education and Self Control on the Consumtif Behavior Students Sebelas Maret University Surakarta - Mulyani, Windi; Indriayu, Mintasih; Wardani, Dewi Kusuma (Economic Education and Entrepreneurship Journal, 2024)
This research aims to analyze the influence of financial literacy, family economic education and self control on the consumtif behavior students Sebelas Maret University Surakarta. This research is a quantitative descriptive study with a population of 30.219 bachelor and vocation UNS students 2021/2022. The sampling technique used in this research was proportionate random sampling which resulted in a sample of 395 respondents. Data collection is carried out through questionnaires. The data analysis used is multiple linear regression analysis with SPSS 25. The results shown from this research are financial literacy has a negative & significant effect on the consumtif behavior UNS students as evidenced by the regression coefficient of -0,487, t value (12,587) > t table (1.966) and sig. (0.000) < 0.05, family economic education has a negative & significant effect on the consumtif behavior UNS students as evidenced by the regression coefficient of -0,433, t value (9,581) > t table (1.966) and sig. (0.000) < 0.05, self control has a negative & significant effect on the consumtif behavior UNS students as evidenced by the regression coefficient of -0,495, t value (6,779) > t table (1.966) and sig. (0.000) < 0.05, financial literacy, family economic education and self control simultaneously has an effect on the consumtif behavior UNS students as evidenced by the calculated F value (123,710) > F table (2.630) and the sig value. (0.000) < 0.05.Keywords: Financial Literacy, Family Economic Education, Consumtive BehaviorDOI: http://dx.doi.org/10.23960/E3J/v7i1.83-87